ASSOCIATION OF SCIENCE TEACHING EFFECTIVENESS IN SPIRAL PROGRESSION APPROACH AND SCIENCE TEACHING EFFICACY BELIEF AMONG SCIENCE TEACHERS - Mariano, Kristopher Rembert Magno; Mina-Roguel, Soledad S. (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Spiral progression approach (SPA), a key element of the K-12 curriculum, aims to gradually reinforce learning by revisiting topics throughout the schooling of learners. Despite efforts, issues persist in the application of SPA, impacting the behavior of junior high school science teachers. The main concerns include the need for training during curriculum restructuring. This study examined the science teaching effectiveness in SPA and the efficacy beliefs of JHS science teachers. Relationships between teaching effectiveness and teaching efficacy were explored among 28 private JHS science teachers in Cabanatuan City, Nueva Ecija. Validity and reliability testing confirmed the consistency of the Self-Perceived Science Teaching Effectiveness Instrument. Teachers scored above average in science teaching effectiveness and teaching efficacy. Correlational analysis revealed a strong association between science teaching effectiveness and teaching efficacy. Specifically, teaching efficacy significantly influenced training and workshops. Sociodemographic factors were not associated with teaching effectiveness in SPA.